1999
DOI: 10.1002/hep.510290226
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Cdk4 and Cdk2 During Rat Liver Regeneration Is Associated With Intranuclear Rearrangements of Cyclin–Cdk Complexes

Abstract: Partial hepatectomy (PH) triggers the entry of rat liver cells into the cell cycle. The signals leading to cell-cycle activation converge into a family of kinases named cyclindependent kinases (cdks). Specific cyclin-cdk complexes are sequentially activated during the cell cycle. Cyclin D-cdk4 and cyclin E-cdk2 are activated during the G 1 phase, cyclin A-cdk2 is activated during the S phase, and cyclin B-cdk1 during mitosis. In the present study, we have examined the timing of the activation of cdk4 and cdk2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
52
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 38 publications
2
52
0
1
Order By: Relevance
“…[3][4][5] Several cyclins and Cdks are activated in the regenerating rat hepatocyte with the peak of DNA synthesis (S phase) occurring around the 24th hour after PH. 6,8,9 Although the activation of some cyclin/Cdk complexes, including cyclin E/Cdk2, might be more specifically associated with the regenerative process itself, 10 there is no direct evidence to date that activation of cyclin E/Cdk2 plays a determinant role in orchestrating cell cycle progression in the regenerating liver. We therefore investigated the impact of targeted inhibition of Cdk2 kinase activity on proliferation of hepatocytes after partial hepatectomy in the rat.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[3][4][5] Several cyclins and Cdks are activated in the regenerating rat hepatocyte with the peak of DNA synthesis (S phase) occurring around the 24th hour after PH. 6,8,9 Although the activation of some cyclin/Cdk complexes, including cyclin E/Cdk2, might be more specifically associated with the regenerative process itself, 10 there is no direct evidence to date that activation of cyclin E/Cdk2 plays a determinant role in orchestrating cell cycle progression in the regenerating liver. We therefore investigated the impact of targeted inhibition of Cdk2 kinase activity on proliferation of hepatocytes after partial hepatectomy in the rat.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] Several studies found an induction of cyclin E and Cdk2 at time points near the G1/S boundary in the regenerating rat hepatocytes. [6][7][8][9] Furthermore, a subcellular rearrangement of cyclins and Cdks is observed in the remnant liver with cyclin E and Cdk2 moving from the cytosol into the nucleus. 6 The cyclin E/Cdk2 complex acts as a histone H1 kinase and the peak of its activity closely correlates with the peak of DNA synthesis in the regenerating hepatocytes.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Cdk1, in association with cyclins A and B, is then essential for entry and exit from mitosis. Cyclin D1 has been shown to be activated by 6 hours and maximal levels of Cdk4 are present at 24 hours after PHx in rats 110. Meanwhile, Cdk1 is sharply induced between 18 and 24 hours, followed by a transient decrease, before another increase at 30 hours post‐PHx in rats 111.…”
Section: The Phases Of Liver Regenerationmentioning
confidence: 98%